Effectiveness Of Corn Cob Charcoal Powder To Reduce Iron (Fe) Levels In Dug Well Water East Dulalowo Village - Ni Nyoman Ardiyanti; Irwan; Moh. Rivai Nakoe (Universitas Muhammadiyah Palu, 2026)
Dug well water is one of the sources of clean water that is used by the community as a water supply facility in daily life. However, the water quality of dug wells often does not meet the requirements, especially in chemical parameters, especially iron content (Fe). High iron levels in water can reduce water quality and increase health and economic problems, so effective, safe and environmentally friendly water management efforts are needed. Corn cobs can be used as activated carbon which acts as a bioadsorbent against iron ion (Fe) pollution. This study aims to test the effectiveness of corn cob charcoal powder in reducing iron (Fe) levels in dug well water with variations in corn cob dosages of 10 grams, 15 grams and 20 grams. The type of true experimental research with a pre-test-post test approach. Iron levels were determined using the spectrophotometry method with three repetitions. Data were analyzed using the Kruskal Wallis test (alpha = 5%). The results of the study showed that the decrease in iron content in the water of the dug well after treatment with a dose of 10 grams with an average value of 0.2341 Mg/L, a dose of 15 grams with an average value of 0.1859 Mg/L, and a dose of 20 grams with an average value of 0.2076 Mg/L This study shows that corn cob charcoal powder is effective in reducing iron levels in dug well water and the dose of corn cob charcoal powder that is effective in reducing iron (Fe) levels in dug well water is the dose 15 grams with a p-value of 0.026 < 0.05, iron content reaches 0.1859 Mg/L and the effectiveness reaches 82%. It is suggested that the community can use corn cob waste as an adsorbent in reducing iron levels and modifying the management of corn cob waste.